Symbolic Moral Self-Completion – Social Recognition of Prosocial Behavior Reduces Subsequent Moral Striving - Susewind, Moritz; Walkowitz, Gari (Frontiers in Psychology, 2020)
According to theories on moral balancing, a prosocial act can decrease people’s motivation to engage in subsequent prosocial behavior, because people feel that they already achieved a positive moral self-perception. However, there is also empirical evidence showing that people actually need to be recognized by others in order to establish and affirm their self-perception through their actions. Without social recognition, moral balancing could possibly fail. In this paper, we investigate in two lab experiments how social recognition of prosocial behavior influences subsequent prosocial striving. Building on self-completion theory, we hypothesize that social recognition of prosocial behavior (self-serving behavior) weakens (strengthens) subsequent prosocial striving. In study 1, we show that a prosocial act leads to fewer subsequent helpfulness when it was socially recognized as compared to not. Conversely, when a self-serving act is socially recognized, it encourages subsequent helpfulness. In study 2, we replicate the effect of social recognition of prosocial acts in an improved and fully incentivized design with a bigger sample: We again find that a socially recognized prosocial act leads to fewer subsequent helpfulness compared to an unrecognized prosocial act. In sum, our results shed a new light on boundary conditions for moral balancing effects and underscore the view that these effects can be conceptualized as a dynamic of self-completion.